2018
DOI: 10.1007/s00221-018-5389-x
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical parameters of the elbow stretch reflex in chronic hemiparetic stroke

Abstract: Introduction: we sought to determine the relative velocity sensitivity of stretch reflex threshold angle and reflex stiffness during stretches of the paretic elbow joint in individuals with chronic hemiparetic stroke, and to provide guidelines to streamline spasticity assessments. Methods: we applied ramp-and-hold elbow extension perturbations ranging from 15-150°/s over the full range of motion in 13 individuals with hemiparesis. After accounting for the effects of passive mechanical resistance, we modeled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…A plethora of stretching approaches exist, which vary in angular range, velocity, repetitions, and frequency ( 22 ). The stretching protocol selected for this study was modeled after one protocol that demonstrated stretch reflex accommodation in the stroke population ( 15 ); this approach is commonly used in quantitative ramp stretching protocols ( 3 , 19 , 23 ). Using this protocol, participants completed a 2 h session on two separate days ( Figures 1B,C ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A plethora of stretching approaches exist, which vary in angular range, velocity, repetitions, and frequency ( 22 ). The stretching protocol selected for this study was modeled after one protocol that demonstrated stretch reflex accommodation in the stroke population ( 15 ); this approach is commonly used in quantitative ramp stretching protocols ( 3 , 19 , 23 ). Using this protocol, participants completed a 2 h session on two separate days ( Figures 1B,C ).…”
Section: Methodsmentioning
confidence: 99%
“…The stretching sequence described above was repeated 20 times at an angular speed of 120°/s to evoke flexor and extensor stretch reflex activity, as determined with sEMG ( 3 , 15 , 24 ) ( Figure 1D ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, the angle at which SRR appears can be determined based on the increase in torque (12)(13)(14). Starsky et al (14) used an isokinetic dynamometer to stretch the elbow flexors of 16 chronic stroke participants at velocities up to 90 /s and, based on the joint stiffness (reflex torque/angle) curve, the onset of SRR was defined as the joint angle at which the stiffness first reached…”
Section: Introductionmentioning
confidence: 99%
“…The onset angle was found inversely correlated with the Ashworth score. McPherson et al (13) also used an isokinetic dynamometer to stretch the elbow flexors of 13 chronic stroke participants at 10 different angular velocities (6 to 150 /s) and defined reflex threshold as the elbow angle at which the torque exceeds 0.2 Nm above the pre-stretch resting torque. A significant negative correlation between the reflex threshold angle and stretching velocity was found in seven participants while one showed a significant positive correlation and five showed no significant correlations.…”
Section: Introductionmentioning
confidence: 99%